A development of halal certification framework using blockchain for monitoring halal certificate in Malaysia - Razali, Amirah Mahirah (2021)
The purpose of this study is to investigate and identify requirements for monitoring halal certification in Malaysia by using Blockchain technology and develop a halal certification framework by using blockchain for monitoring halal certificates in Malaysia. Researchers have studied every factor that influences information retrieval, communicative factors that include consumer confusion, consumer awareness, consumer attitudes towards halal products, and the level of individual religion are considered because halal issues are closely related to a Muslim. These factors are rarely taken care of today, especially Muslims who are required to comply with the law set by violating halal and haram. The interview method is done in a fast-food restaurant. This project conducted fast-food restaurant owners’ interview methods and validation against other models to validate the framework. SHA-256 algorithm with hashing techniques has been used to secure halal certificates. This study found that organizational performance in the halal nutrition industry in Malaysia is influenced by various factors whether management factors through the blockchain-based halal certification approach in Malaysia, human capital factors, and also the organization’s internal operations practices. Therefore, it is not surprising that the Malaysian government has outlined in the Malaysian Halal Certification Procedure Manual to overcome problems at the operational level. Finally, the issues concerning the blockchain-based halal certification in Malaysia are relevant, in ensuring that goods manufactured in line with halal standards and are acceptable to scholars, researchers, management and halal certification bodies, politicians, and the community.